Pa’loly sebagai Tradisi Hari Meninggal Ke 3,7 dan Ke 9 di Negeri Hila Kecamatan Leihitu Kabupaten Maluku Tengah - Muhammad Idul Launuru (Journal on Education, 2023)
The tradition in Negeri Hila, which is known as the Pa'loly tradition, is usually carried out on the 3rd, 7th and 9th days of death in Negeri Hila, Leihitu District, Central Maluku Regency. Pa'loly is usually called gotong royong and is carried out to help fellow human beings in a job without being invited they immediately flock to work together, this tradition also aims to relieve people who have a celebration. Apart from that this tradition is also useful for speeding up work results that cause a burden for people who have a celebration. The type used in this research is descriptive qualitative type. This method basically aims to understand the condition and life of the people in Negeri Hila, Leihitu District, Central Maluku Regency. The qualitative method is fact-finding with clear and precise interpretations, to make a systematic, factual and accurate description of the Pa'loly Tradition. The instruments used were observation, interviews and documentation. The data analysis used is qualitative data analysis which consists of data reduction, data presentation, and drawing conclusions. On this day of death, after the body is buried at night, especially the fathers in the Land of Lost, they will come in droves to the funeral home to bring money to the bereaved family and they will bring the money voluntarily, whatever they bring will be appreciated by the party left behind, this is called in hila language, namely tanate money. Here they never judge people who can afford it and people who can't afford it. They only bring money voluntarily, never make comparisons.